2020
DOI: 10.1002/dc.24571
|View full text |Cite
|
Sign up to set email alerts
|

Acinic cell carcinoma of the salivary gland associated with lymphoid‐rich stroma. A diagnostic dilemma on cytology: Study of two cases

Abstract: A lymphoid‐rich stroma is a common finding in salivary gland tumors. Several reports documented this association with acinic cell carcinoma (ACC). However, cytologic studies reporting this phenomenon are rare and mainly confined to sporadic single case reports. We present the cytologic features of two cases of ACCs of the parotid gland displaying a lymphoid‐rich background and discuss the cytologic differential diagnoses of this uncommon ACC variant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…21 The abundance of this lymphoid population can lead to a sampling error and potential misdiagnosis of ACC with FNA or core needle biopsy. 22,23 Anecdotally, 1 patient in this series had an initial FNA of his left parotid mass diagnosed as reactive lymphoid hyperplasia with confirmatory normal flow cytometry. Because no tissue follow-up occurred, that aspirate is not included as part of our series, but when he returned 6 years later with a large mass in the same region diagnosed as high-grade carcinoma (case 38) and subsequently confirmed as ACC-HGT with metastases to mediastinal lymph nodes (cases 39 and 40), it was tempting to speculate that tumor-associated lymphoid proliferation was responsible for a latent conventional ACC not being recognized during his initial presentation.…”
Section: Discussionmentioning
confidence: 95%
“…21 The abundance of this lymphoid population can lead to a sampling error and potential misdiagnosis of ACC with FNA or core needle biopsy. 22,23 Anecdotally, 1 patient in this series had an initial FNA of his left parotid mass diagnosed as reactive lymphoid hyperplasia with confirmatory normal flow cytometry. Because no tissue follow-up occurred, that aspirate is not included as part of our series, but when he returned 6 years later with a large mass in the same region diagnosed as high-grade carcinoma (case 38) and subsequently confirmed as ACC-HGT with metastases to mediastinal lymph nodes (cases 39 and 40), it was tempting to speculate that tumor-associated lymphoid proliferation was responsible for a latent conventional ACC not being recognized during his initial presentation.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover,10%-29% of AciCCs are associated with TALP, which may lead to misdiagnoses of the tumors as reactive lymph nodes. 5,6 Some studies have shown that the diagnosis of AciCC was correctly made in only two-thirds of the cases, largely due to the absence of conventional serous acinar morphology and/or lack of ancillary studies. 18 Indeed, FNAC of AciCC is not infrequently categorized as oncocytic/oncocytoid SUMP (category IVB) in the Milan System.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the delicate cytoplasm of the neoplastic epithelial cells, cytologic preparations of AciCC may yield tumor cells with stripped bare nuclei, which may resemble lymphocytes, particularly on conventional smear preparations. Moreover,10%–29% of AciCCs are associated with TALP, which may lead to misdiagnoses of the tumors as reactive lymph nodes 5,6 . Some studies have shown that the diagnosis of AciCC was correctly made in only two‐thirds of the cases, largely due to the absence of conventional serous acinar morphology and/or lack of ancillary studies 18 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations